First record of the genus Genaemirum (Hymenoptera, Ichneumonidae, Ichneumoninae) from West Africa, with the description of a new species from Guinea - Davide Dal Pos; Pascal Rousse (European Journal of Taxonomy, 2018)
A new species of the Afrotropical genus Genaemirum Heinrich, 1936 is described from a single female specimen from Guinea and compared to the closest species, G. rhinoceros Heinrich, 1967. Genaemirum filipazzii sp. nov. also provides the first record of the genus for West Africa. An updated key to the species is included.